POTENSI MIKROBA PENITRIFIKASI KAWASAN PERTAMBAKAN UDANG TANJUNG PASIR, TANGERANG - Komarawidjaja, Wage; Ambarsari, Hanies (Jurnal Teknologi Lingkungan, 2001)
High concentration of ammonia in shrimps pond sediment due to the accumulation of feed excessive will become negative impact to the shrimp culture. Therefore, increasing the indigenous microbial abilities in minimizing toxicity effect of ammonia through biotransformation of ammonia into nitrite and nitrate is very important for shrimp growth and health.Isolation and identification of nitrifying microbes has been done. The number of microbes isolated form shrimps pond are six namely 2p, 2k, 3p, 1p, 3k, and 2. The number of isolated microbes in aquaculturing pond (T-bd) is five and in post harvest pond (T-pp) is three.In T-bd samples, autotroph nitrifying microbes are 2(k), 2(p) and 3(p), but 1(p) and 3(k) as heterotroph nitrifying microbes. And in T-pp samples, autotroph nitrifying microbe is 3(p), except 2 and 3(k) as heterotroph nitrifying microbes. The rank of effectivness In nitrifying activity is 2k, 3p and 2p respectively.